Optimization and validation of a robust human T cell culture method for monitoring phenotypic and polyfunctional antigen-specific CD4 and CD8 T-cell responses - Lin, Yun (2009)
BACKGROUND: Monitoring cellular immune responses is one prerequisite for the rational development of cancer vaccines. METHODS: Here, we describe an extensive effort to optimize and quantitatively validate an in vitro T cell culture method by determining the phenotype and function of both CD4(+) and CD8(+) T cells, including the measurement of the phenotype markers CCR7, CD45RA, CD28 and CD27 and of the functional markers IFN-γ, IL-2, MIP-1β, TNF-α and CD107a. RESULTS: Autologous PBMCs are potent stimulators that expand antigen-specific CD8(+) T cells during short-term culture with the addition of IL-2 and IL-15 cytokines. Polyfunctional antigen-specific CD4(+) and CD8(+) T cells are detectable using this method. DISCUSSION: Our culture system represents a robust human T cell culture protocol which permits phenotypic, quantitative and qualitative evaluation of vaccine-induced CD4(+) and CD8(+) T cell responses.